1990
DOI: 10.1128/jcm.28.6.1292-1296.1990
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal slime: a cautionary tale

Abstract: Slime production by Staphylococcus epidermidis may be important in the adherence to and colonization of biomedical devices, and slime has been proposed to have various effects on the immune system. Attempts were made to isolate, purify, and chemically characterize slime from S. epidermidis cultivated under fluid on tryptic soy broth-agar medium. "Crude slime" from slime-producing strain RP-12 was characterized by a high galactose content. Similar materials in similar yields were isolated from slime-producing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 33 publications
0
23
0
3
Order By: Relevance
“…In the literature, many authors stress the influence of the in vitro conditions of experiments on the biochemical constitution of the bacteria, especially capsule formation [5,6,27] and the importance of the solid media in duplicating in vivo conditions [28]. Another advantage of a solid medium recovered by a cellophane membrane, as we used, is to avoid contaminants from medium components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, many authors stress the influence of the in vitro conditions of experiments on the biochemical constitution of the bacteria, especially capsule formation [5,6,27] and the importance of the solid media in duplicating in vivo conditions [28]. Another advantage of a solid medium recovered by a cellophane membrane, as we used, is to avoid contaminants from medium components.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of a chemically defined medium for slime production has been demonstrated in studies of Staphylococcus epidermidis slime [5,6]. In previous works about alginate from P. aeruginosa, the strains used as the source of alginate have been grown in various liquid or solid media, and the extraction and purification procedures have also differed widely resulting in varying results for the chemical composition [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal and in vitro experiments, crude slime preparations have been reported to interfere with host defence mechanisms [81,82]. However, the results of the studies of Drewry et al [77] and Hussain et al [34] demand the reassessment of the suggested biological properties of slime [44]. Slime prepared by growing bacteria on complex media solidified with agar has been used in many in vitro and animal studies [81][82][83][84][85][86].…”
Section: Biological Effects" Of Slimementioning
confidence: 99%
“…Such results confirm that much of the material which hitherto has been regarded as staphylococcal slime is really agar. Drewry et al [77] have independently reported their suspicion that slime isolated from media solidified with agar is very heavily contaminated with agar. Thus the use of a chemically defined medium (if it is solidified with agar) does not completely overcome the problem of spurious high molecular mass material, because the agar remains a potential source of foreign material.…”
mentioning
confidence: 99%